1997
DOI: 10.1145/263867.263489
|View full text |Cite
|
Sign up to set email alerts
|

Closure properties of constraints

Abstract: Many combinatorial search problems can be expressed as "constraint satisfaction problems" and this class of problems is known to be NP-complete in general. In this paper, we investigate the subclasses that arise from restricting the possible constraint types. We first show that any set of constraints that does not give rise to an NP-complete class of problems must satisfy a certain type of algebraic closure condition. We then investigate all the different possible forms of this algebraic closure property, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
388
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 424 publications
(391 citation statements)
references
References 21 publications
3
388
0
Order By: Relevance
“…In [2] (see [7] for a simpler proof), it was shown that for every Malt'sev operation ϕ, CSP(Inv(ϕ)) is solvable in polynomial time. This general result encompasses some previously known tractable cases of the CSP, such as CSP with constraints defined by a system of linear equations [23] or CSP with near-subgroups and its cosets [19,18].…”
Section: Dalmaumentioning
confidence: 70%
“…In [2] (see [7] for a simpler proof), it was shown that for every Malt'sev operation ϕ, CSP(Inv(ϕ)) is solvable in polynomial time. This general result encompasses some previously known tractable cases of the CSP, such as CSP with constraints defined by a system of linear equations [23] or CSP with near-subgroups and its cosets [19,18].…”
Section: Dalmaumentioning
confidence: 70%
“…This work has led to the identification of a number of classes of constraints which are tractable, in the sense that there exists a polynomial time algorithm to determine whether or not any collection of constraints from such a class can be simultaneously satisfied [2,12,20,27]. One powerful result in this area establishes that any tractable class of constraints over a finite domain must be preserved by a non-trivial algebraic operation, known as a polymorphism [4,19,20].…”
Section: Examplementioning
confidence: 99%
“…For example, the notion of a multimorphism can be used to characterise tractable subproblems in all of the following areas: in the case of the Satisfiability problem these include the Horn-Sat and 2-Sat subproblems [15]; in the case of the standard constraint satisfaction problem these include generalisations of Horn-Sat (such as the so-called 'max-closed' constraints [23,20]), generalisations of 2-Sat (such as the so-called '0/1/all' or 'implicative' constraints [8,18,25]) and systems of linear equations [20]; in the case of the optimisation problem Max-Sat these include the '0-valid' and '2-monotone' constraints [9]; in the case of optimisation problems over sets these include the submodular set functions [17,26] and bisubmodular set functions [14].…”
Section: Examplementioning
confidence: 99%
See 2 more Smart Citations